Two Years Under Jokowi – Jokowi’s Power Consolidation: At What Cost? - Syailendra, Emirza Adi (2016)
Starting weak, over the course of two years, Indonesia’s seventh president Joko Widodo (Jokowi), has been able to solidify his power. This victory, however, has come at several costs.